2019
DOI: 10.5614/j.math.fund.sci.2019.51.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Method and Characterization of Phycocyanin Pigment from Spirulina platensis

Abstract: Spirulina platensis is a microalgae species that contains phycocyanin, a blue pigment that is widely used in the food, cosmetic and pharmaceutical industries. The objective of this study was to isolate phycocyanin from dried biomass of Spirulina platensis. The optimum extraction was through freezethawing extraction with 0.01 M phosphate buffer pH 7. Purification was done using 50% ammonium sulphate precipitation, dialysis, and gel filtration chromatography. The purity ratio of the purified product was 1.729 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This process was repeated 2-3 times. After the freeze-thawing cell disruption period, samples were centrifuged, and aliquots were separated to analyze phycocyanin by UV-Vis spectroscopy (Thermo Fisher Scientific, Waltham, MA, USA) [19]. A UV-Vis spectrophotometer was used to measure the absorbance of the extracts at wavelengths 280, 615, 620, and 652 nm, respectively.…”
Section: Extraction Of Chlorophyll-a and Chlorophyll-b Total Caroteno...mentioning
confidence: 99%
“…This process was repeated 2-3 times. After the freeze-thawing cell disruption period, samples were centrifuged, and aliquots were separated to analyze phycocyanin by UV-Vis spectroscopy (Thermo Fisher Scientific, Waltham, MA, USA) [19]. A UV-Vis spectrophotometer was used to measure the absorbance of the extracts at wavelengths 280, 615, 620, and 652 nm, respectively.…”
Section: Extraction Of Chlorophyll-a and Chlorophyll-b Total Caroteno...mentioning
confidence: 99%
“…An acetate buffer at a pH of 5 is occasionally employed as a buffer for C-PE extraction [ 86 ]. However, research by Julianti et al (2019) and Zavrel et al (2018) demonstrated that the C-PC yield and purity extracted with an acetate buffer are lower than that extracted with a phosphate buffer [ 87 , 88 ]. A comparatively low-cost, double-distilled water was shown to extract the highest quantity of C-PC, with no significant difference in comparison to PC amounts extracted using a phosphate buffer [ 89 ].…”
Section: Downstream Processing Of C-pementioning
confidence: 99%
“…The US Food and Drug Administration (FDA) has regulations to employ the phycocyanin pigment obtained from Spirulina platensis as color additive in gum, toffee and other food items (Julianti et al, 2019;Spolaore et al, 2006).…”
Section: Pigmentsmentioning
confidence: 99%